Sea-level change and the archaeology of early Venice - Ammerman, A. J.
The threatened city of Venice, plauged by rising sea levels and subsiding ground, has been the subject of recent archaeological investigation. Studies of buried archaeological sites yield new evidence on trends in sea-level change for the Lagoon of Venice and provide important insight into how early habitation responded to such change.